Strengthening patient outcome evidence in health technology assessment: a coproduction approach. (13th January 2021) - Rasburn, Mark; Livingstone, Heidi; Scott, Sarah E.
Abstract: The National Institute for Health and Care Excellence (NICE) worked with patients and staff from six patient organizations to review existing health technology assessment (HTA) methods and coproduce proposals to improve the following: patient involvement, how patient evidence is identified and considered by committees, and the support offered to patient stakeholders. This engagement identified important factors that HTA bodies need to understand to enable meaningful patient and public involvement (PPI), such as having clearly documented processes, appropriate evidence submission processes, transparent decisions, and suitable support. This work demonstrated the benefits of HTA bodies working collaboratively with patient stakeholders to improve PPI. By doing so, HTA bodies can increase their knowledge and understanding of the barriers faced by patient stakeholders to develop appropriate solutions to remove them. The coproduction approach improved stakeholder engagement methods, provided a better analysis of data, supported the development of meaningful conclusions, and improved stakeholder relationships.